Butterflies and moths - Carter, David J. (David James), 1943-; Greenaway, Frank (New York : Dorling Kindersley ; Boston, Mass. : Distributed by Houghton Mifflin Company, 1992)
A field guide to butterflies and moths around the world, each depicted by a full-color photograph with a caption that describes key features and points of differentiation.
Includes index.
Keywords: Butterflies -- Identification -- Juvenile literature; Moths -- Identification -- Juvenile literature; Butterflies -- Identification; Moths -- Identification